Expanding the Chemical Diversity of Stemona parviflora: Isolation and Characterization of New Parvistemoline-Type Alkaloids - Shuaizhen Zhou; Ruolin Geng; Changqiang Ke; Fan Ge; Ying Chen; Chunping Tang; Yang Ye (Chemistry)
A comprehensive phytochemical investigation of the whole plant of Stemona parviflora led to the isolation of 13 alkaloidal constituents, including five new alkaloids, parvistemonines B–F (1–5). The structures of these compounds were elucidated through extensive analyses of 1D and 2D NMR spectra, DFT NMR calculation, and comparisons with data in the literature. Notably, compounds 1–4 represent new examples of the rare parvistemoline-type alkaloids, with compound 4 showcasing a unique rearranged skeleton. Additionally, parvistemonine F (5) was identified as a distinct alkaloid skeleton characterized by a n-butyl side chain. These findings significantly expand our understanding of the chemical diversity of parvistemoline-type alkaloids and provide clues for elucidating the biosynthetic pathways of these structurally unique parvistemoline alkaloids.